HealthLit4Kids: Dilemmas associated with student health literacy development in the primary school setting. (March 2021) - Nash, Rose; Cruickshank, Vaughan; Pill, Shane; MacDonald, Abbey; Coleman, Cheryn; Elmer, Shandell
Objective: To ascertain teachers' articulation and experiences of navigating dilemmas that inhibit and/or enable the fostering of health literacy in primary school settings. Design: Qualitative analysis of teachers' written reflections on introducing health literacy into their school and classroom. Setting: Tasmania, Australia. Method: Eighty-four teachers in five primary schools participated in the HealthLit4Kids programme. Teacher reflections were collected at the conclusion of the first year of the programme and assessed using Windschitl's Dilemmas to identify recurrent themes raised by the conceptual, pedagogic, cultural and political dilemmas teachers faced. Results: Key dilemmas faced by teachers concerned the development of a whole-of-school approach, student engagement and professional development. Conclusion: Internationally few health literacy programmes for primary schools exist. The theory developed from the themes identified in this study will inform future health literacy programme design and implementation strategies. Purposeful consideration of each theme will guide their success, scalability and sustainability. Future research on the role of constructivist teaching styles in health literacy development in the school setting is urgently required.